New Trends in the Protection of the Antarctic Environment: The 1991 Madrid Protocol - Blay, S. K. N. (American Journal of International Law, 1992)
In June 1991, the Antarctic Treaty states, meeting in Madrid, Spain, approved the Protocol on Environmental Protection to the Antarctic Treaty (the Madrid Protocol). The Protocol was adopted by the Antarctic Treaty Consultative Parties and opened for signature on October 4, 1991. Negotiated over a three-year period, the Protocol, together with its annexes, is the most comprehensive multilateral document ever adopted on the international protection of the environment. It promises to be a significant blueprint for preserving the Antarctic. An ironic feature of the Protocol is that, while it bans mining in Antarctica, it had its origins in the 1988 Convention for the Regulation of Antarctic Mineral Resource Activities (CRAMRA), which permitted mining.